Efficacy and safety of oral tadalafil in the treatment of men in Canada with erectile dysfunction: a randomized, double-blind, parallel, placebo-controlled clinical trial - Carrier, Serge; Brock, Gerald B; Pommerville, Peter J; Shin, Janey; Anglin, Greg; Whitaker, Steven; Beasley, Jr, Charles M (Journal of sexual medicine, 2005)
Erectile dysfunction (ED) is a highly prevalent, often undertreated condition. This 12-week, double-blind, parallel, placebo-controlled study was conducted at 25 sites in Canada to evaluate the efficacy and safety of oral tadalafil, a phosphodiesterase type 5 inhibitor, for the treatment of ED. Men with ED of organic, psychogenic, or mixed etiology were stratified by baseline ED severity then randomly assigned to placebo (N = 50), tadalafil 10 mg (N = 103), or tadalafil 20 mg (N = 100), taken as needed (maximum, once daily). Efficacy was assessed by the International Index of Erectile Function (IIEF), a Sexual Encounter Profile diary, and a global assessment question (GAQ). Tadalafil 10 mg and tadalafil 20 mg significantly improved erectile function compared with placebo (P < 0.001, all measures). At end point, the mean IIEF erectile function (EF) domain scores were 14.5, 21.2, and 23.3 of a possible score of 30 for placebo, tadalafil 10 mg, and tadalafil 20 mg, respectively. Patients treated with tadalafil reported greater change from baseline on the IIEF EF domain score compared with placebo, regardless of baseline ED severity. During treatment, the mean per-patient proportion of successful intercourse attempts was higher for tadalafil 10 mg and 20 mg than for placebo (placebo, 31.9%; tadalafil 10 mg, 56.7%; and tadalafil 20 mg, 61.5%), and a greater proportion of patients reported improved erections with tadalafil (GAQ; placebo, 22.0%; tadalafil 10 mg, 67.0%; tadalafil 20 mg, 79.0%). Fifty percent and 62% of patients treated with tadalafil 10 mg and 20 mg, respectively, achieved successful sexual intercourse after their first dose, compared with 31% with placebo. Treatment-emergent adverse events were generally mild or moderate. Tadalafil was an effective, well-tolerated therapy for ED of broad-spectrum etiology and severity.